Neuroprotective Activity of a Non-Covalent Imatinib+TP10 Conjugate in HT-22 Neuronal Cells In Vitro - Izabela Rusiecka; Iwona Gągało; Ivan Kocić (MDPI AG, 2024)
This study evaluated the probable relevance of a non-covalent conjugate of imatinib with TP10 in the context of a neuroprotective effect in Parkinson's disease. Through the inhibition of c-Abl, which is a non-receptor tyrosine kinase and an indicator of oxidative stress, imatinib has shown promise in preclinical animal models of this disease. The poor distribution of imatinib within the brain tissue triggered experiments in which a conjugate was obtained by mixing the drug with TP10, which is known for exhibiting high translocation activity across the cell membrane. The conjugate was tested on the HT-22 cell line with respect to its impact on MPP+-induced oxidative stress, apoptosis, necrosis, cytotoxicity, and mortality. Additionally, it was checked whether the conjugate activated the ABCB1 protein. The experiments indicated that imatinib+PEG4+TP10 reduced the post-MPP+ oxidative stress, apoptosis, and mortality, and these effects were more prominent than those obtained after the exposition of the HT-22 cells to imatinib alone. Its cytotoxicity was similar to that of imatinib itself. In contrast to imatinib, the conjugate did not activate the ABCB1 protein. These favorable qualities of imatinib+PEG4+TP10 make it a potential candidate for further in vivo research, which would confirm its neuroprotective action in PD-affected brains.